"Bacterial Consortium": A Potential Evolution of Fecal Microbiota Transplantation for the Treatment of Clostridioides difficile Infection. (8th August 2022) - Quaranta, Gianluca; Ianiro, Gianluca; De Maio, Flavio; Guarnaccia, Alessandra; Fancello, Giovanni; Agrillo, Chiara; Iannarelli, Federica; Bibbo, Stefano; Amedei, Amedeo; Sanguinetti, Maurizio; Cammarota, Giovanni; Masucci, Luca
Abstract : Fecal microbiota transplantation (FMT) consists of infusion of feces from a donor to a recipient patient in order to restore the resident microbial population. FMT has shown to be a valid clinical option for Clostridioides difficile infections (CDI). However, this approach shows several criticalities, such as the recruiting and screening of voluntary donors. Our aim was to evaluate the therapeutic efficacy of a synthetic bacterial suspension defined "Bacterial Consortium" (BC) infused in the colon of CDI patients. The suspension was composed by 13 microbial species isolated by culturomics protocols from healthy donors' feces. The efficacy of the treatment was assessed both clinically and by metagenomics typing. Fecal samples of the recipient patients were collected before and after infusion. DNA samples obtained from feces at different time points (preinfusion, 7, 15, 30, and 90 days after infusion) were analyzed by next-generation sequencing. Before infusion, patient 1 showed an intestinal microbiota dominated by the phylum Bacteroidetes . Seven days after the infusion, Bacteroidetes decreased, followed by an implementation of Firmicutes and Verrucomicrobia . Patient 2, before infusion, showed a strong abundance of Proteobacteria and a significant deficiency of Bacteroidetes and Verrucomicrobia . Seven days after infusion, Proteobacteria strongly decreased, while Bacteroidetes and Verrucomicrobia increased. Metagenomics data revealed an "awakening" by microbial species absent or low concentrated at time T0 and present after the infusion. In conclusion, the infusion of selected bacteria would act as a trigger factor for "bacterial repopulation" representing an innovative treatment in patients with Clostridioides difficile infections.